Africa and the international criminal court - Werle, Gerhard; Fernandez, Lovell; Vormbaum, Moritz (International Criminal Justice Series ;, 2014)
In November 2013, the South African-German Centre for Transnational Criminal Justice hosted a conference on Africa and the International Criminal Court, in Cape Town, South Africa. The theme of the Conference was the strained relationship between African states, represented by the African Union (AU), and the International Criminal Court (ICC). This relationship started promisingly but has been in crisis in recent years. This book sheds light on the present frictions between the AU, the ICC and the UN Security Council. Eminent experts in the field of international criminal justice, including judges and prosecutors of the ICC and other African judicial bodies, as well as international criminal law scholars, analyze and debate the achievements and shortcomings of interventions by the ICC in Africa. They propose ways in which international courts and domestic courts within and outside of Africa can cooperate and address fundamental issues of international criminal law, such as the implementation of the Rome Statute, deferrals of cases before the International Criminal Court and the prosecution of crimes by third states on the basis of universal jurisdiction. Researchers and practitioners in the field of international criminal law and related disciplines will benefit from the high-level experiences and proposals brought together in this volume. For students with a focus on criminal law and its international implications it is a source of information and challenges.